Von der Macht der Sätze – Sprachkritische Betrachtungen zum Drama Kaspar von Peter Handke - Schmidt, Patrícia (Contingentia, 2008)
The article “Von der Macht der Sätze – Sprachkritische Betrachtungen zum Drama Kaspar von Peter Handke“ written by Patricia Schmidt analyses the poetical review of language that is given in the named play. The centre of attention is how Handke forms his sceptical opinions about language into a provoking play and how he is influenced by the philosophical review of language like “Beiträge zu einer Kritik der Sprache” written by Fritz Mauthner, an almost forgotten philosopher of the beginning of the 20th century.